Industrial training report: Universiti Kebangsaan Malaysia (UKM) / Nur Aizatul Azwa Rahim - Rahim, Nur Aizatul Azwa (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This report is about my industrial training experience at the Administration and Facilities Division of the UKM Registrar's Department. This training lasts two months during the students' semester break following the completion of Semester four. After completing industrial training, students are asked to present what they learned in the industry. Students are also allowed to choose the industry they are interested in to undergo practical training. The purpose of this industry training is to teach students about how work in the real world works and make them improve their skills throughout it.